v.1 - Hulme, David; Mosley, Paul (London, 1996)
In two volumes these books review and expand the theory that poverty in the world's poorest regions could be alleviated by providing small loans to micro-entrepreneurs. Volume 1 provides detailed analysis of this theory and offers policy recommendations for practitioners in this field. Volume 2 presents empirical evidence drawn from comparative experiences in seven developing countries. The work assesses the success of this policy and provides some startling conclusions. This is essential reading for all those interested in development, poverty-reduction, social welfare and finance.
Keywords: Poverty